MITOCHONDRIAL DNA (MTDNA) VARIATION OF SULAWESI BLACK MACAQUE (Macaca nigra) LIVED IN TWO NATIONAL PARKS (TANGKOKO AND DUA SAUDARA) OF NORTH SULAWESI - Hapry F.N. Lapian (The East Java Biological Society, 2011)
Hypervariable II (HVII) regions of mitochondrial DNA (mtDNA) D-loop regions of Macaca nigra lived in Tangkoko and Dua Saudara National Parks have been analysed. An approximately 600 base pairs (bp) of HVII regions was sequenced to characterize genetic variation among 20 samples of Macaca nigra lived in Tangkoko and Dua Saudara National Parks. Using an outgroup of Macaca fascicularis of Kalimantan, a neighbor-joining and maximum parsimony trees both identified that all DNA samples of Macaca nigra were arranged in similar cluster. The low nucleotide diversity among samples of Macaca nigra in Tangkoko and Dua Saudara suggests either there is a direct mix among species or that they may have similar ancestor among them.